Financial inclusion and economic growth in Vietnam: Evidence across provinces and income groups - Luong, Thi Thuy Huong; Lerskullawat, Attasuda; Nguyen , Thi Anh Nhu (Economics and Business Review, 2025)
This research aims to examine the effect of financial inclusion on economic growth in Vietnam. Using panel data from 63 provinces during 2014–2020, estimations are conducted for both the full sample and across two income groups. Financial inclusion is measured by indicators capturing geographical penetration and using products and services in commercial banks and insurance. The difference-GMM estimation results demonstrate that financial inclusion captured by higher commercial bank branches and using bank accounts, saving passbooks, and ATM cards present significant positive effects on economic growth in Vietnam. In contrast, participating life and non-life insurance shows a non-significant effect. For high-income provinces, participating in life and non-life insurance positively affects economic growth. In addition, the study indicates robust effects of commercial bank branch penetration and using ATM cards in enhancing economic growth in both low-income and high-income localities.